Analysis of Strength of VDA 4500 Type Container Palletizing Robot Manipulator Gripper - Urbonas, Klaidas; Rimovskis, Sergejus; Sabaliauskas, Arturas (Jaunųjų mokslininkų darbai, 2021)
An analysis of the company’s existing palletizing process has been performed, and the most appropriate method of process modernization has been selected accordingly. Also, a robot was selected according to the type of container to be palletized and its weight. A prototype of a robot manipulator gripper has been designed. The load calculation of the gripper levers was performed, the pneumatic cylinders for the lever control were selected. Lever strength analysis was also performed. The gripper mass was determined.